Analysis of the target achievement level of public services levy related waste services. Study on the government of tolitoli, central sulawesi. - Edi Yanto; Fahri Eka Oktora; A. Irfan Efendi (Institute of Computer Science (IOCS), 2022)
This type of research is a quantitative descriptive study with the aim of analyzing and knowing the level of achievement of the target of public service retribution through the Tolitoli Regency Government Cleaning Service Fee in 2019-2021. With a quantitative approach and TPT formulation, the results obtained in the form of a trend of achievement fluctuations for three years. In 2019 the acceptance of the cleaning retribution did not reach the predetermined target with a TPT of 82.73%, while in 2020 the revenue even exceeded the initial target with an TPT of 105.29%. Furthermore, in 2021 it will decrease with the TPT achievement of 94%. This proves that the performance of retribution for cleaning services in Tolitoli Regency still needs to be maximized for the next few years.